Studies in the Aramaic Legal Papyri from Elephantine - Muffs, Yochanan (1969)
= 28; 246; untersucht im Hauptteil den aram. Terminus ṭyb lbby und seine akk. Entsprechung libbašu ṭāb; in Kap. VII werden The Origins of Aramaic Common Law Formularies (p. 179-194) vor allem in nA Rechtsurkunden nachgewiesen. 233-243: Index of Cuneiform Terms; 247-254: Index of Cuneiform Sources.